Multi-OMICS and Molecular Biology Perspective in Buffalo Genome - Sikdar, Suranjana; Das, Tuhin; Sajib, Emran Hossain; Rahman, Kazi Mahbub Ur Rahman; Siddik, AMAM Zonaed; Uddin, Md Bashir (Journal of Buffalo Science, 2021)
The bovine species buffalo was domesticated from its wild strain Bubalus arnee and is widely used livestock in southern Asia. There are two distinct types of Buffalo- the swamp buffalo (B. bubalis kerebau) and the river buffalo (B. bubalis bubalis), which diverged from the wild Asian water buffalo and then evolved in separate geographical regions. Several research studies performed on buffalo, like- characterization of trait-specific Single Nucleotide Polymorphism (SNP), genetic and phenotypic diversity, gene prediction and function annotation, mapping of the draft genome, have helped our understanding of the buffalo genome. Some advanced discovery as identification of Single Nucleotide Variant (SNVs), Simple Sequence Repeats (SSR) marker and their association with various phenotypic traits, MicroRNA’s expression profiling, whole-genome sequencing, etc. have also enabled us to track the chromosomal evolution, physiological processes, and gene expression of buffalo. Proper enhancement of these traits can lead us to apply multi-omics-based tools for better animal health and production. Recent advancement in genomic research on buffalo is being accelerated with the association of modern tools like- Genome-Wide Association Study (GWAS), genotyping by sequencing, epigenomic screening, microRNA’s expression profiling, microarray technology, and whole-genome sequencing. All these tools bear great significance in breed up-gradation, identification of the phylogenetic relationship between species in proteome and genomic level, study gene expression level, diagnose diseases or developmental stages, phenotypic diversity, etc. All this knowledge paved the way for better optimization of production efficiency, product quality, and resistance to certain health hazards.